(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article focuses on the violation of human rights taking place along Italy’s maritime border, looking in particular at the illegal practices that have occurred in the Lampedusa hotspot. To illustrate the legal obligations to which European states are bound we examine the most recent jurisprudence issued by the Strasbourg Court, in particular the judgement J.A. and Others v. Italy.